Verbal Strategies in Building a Trainer's Impression in the Opening Session of Training - Fauzi Noerwenda; Anne Maryani; Oji Kurniadi (MIMBAR : Jurnal Sosial dan Pembangunan, 2025)
Training sessions are crucial moments for trainers to help participants improve their skills and confidence. Trainers at Persona Public Speaking are responsible for enhancing participants’ speaking abilities to become more effective and impactful. One key aspect of this process is the trainer’s ability to create a strong first impression through verbal communication strategies at the beginning of the session. A positive first impression can establish a comfortable learning atmosphere, motivate participants, and strengthen the trainer’s credibility. This study aims to analyze the verbal strategies used by trainers in creating first impressions during training sessions. Using a descriptive qualitative approach, four trainers from Persona Public Speaking were involved as research subjects. Data was collected through observation and in-depth interviews, then analyzed using Miles and Huberman’s interactive model. The results show that the use of formal greetings, opening rhymes, analogies, and acronyms forms part of the verbal strategies effectively used to capture attention and foster emotional closeness among participants. Furthermore, diction adjustments based on participant profiles and the influence of role models also shape the trainers’ communication styles. These findings highlight the importance of mastering verbal communication strategies as a core competency for trainers in adult learning contexts, as well as the critical role of early verbal choices in creating positive impressions while providing practical contributions to the development of effective, communication-based training.